Acute aortic valvulitis as an initial presentation of systemic lupus erythematosus - Louthrenoo W. (2014)
Valvular involvement in patients with systemic lupus erythematosus (SLE) is not uncommon but patients rarely present with it. The mitral valve is most commonly involved. We report a 36-year-old man who had an episode of acute fever, arthritis, and acute aortic insufficiency with a small vegetation at the tip of the aortic valve mimicking infective endocarditis, proven later to be due to SLE. SLE should be considered as one of the uncommon causes of acute aortic insufficiency.